Promoting Speaking Skills Through English Storytelling in Madrasah Diniyah: An Islamic Non-Formal School in Indonesia - Farid Noor Romadlon; Akhmad Khairul Azmi (LPPM Universitas PGRI Semarang, 2024)
Since English is used frequently in everyday life, exposure to it is essential in non-formal education. Using storytelling techniques and incorporating English as local content can help create a new learning environment and combat boredom that stems from formal school fatigue. This study investigated how English storytelling can enhance speaking ability and foster a positive attitude toward learning English among non-formal school students. The research involved 52 students at Madrasah Diniyah, an Islamic non-formal school in Central Java utilizing test, questionnaire, and parent interviews. The research findings showed that the English Storytelling Technique can increase students' motivation to learn in non-formal schools and also improve their speaking ability. This is evidenced by the significant improvement in students' speaking ability, increasing from the initial level of 55% to 87% at the final level. The student's parents believe that because the Islamic non-formal school offers English language instruction, their children are more encouraged to learn the language. Therefore, the study suggests that the exposure of English learning should be given more and intensively to non-formal school in the future learning.